Energy: Rhetoric's Vitality. Issue 3 (27th May 2018) - Ingraham, Chris
Abstract : From its outset in antiquity, rhetorical energy has been a protean concept : energeia concerning the vitality of speech, and the related enargeia referring to vivid description. Recent interest in affect, the Anthropocene, new materialism, and the more-than-human has only made "energy" more salient, yet more promiscuously evoked than ever. Notwithstanding the concept's centrality to some major works of contemporary scholarship, the importance of energy to rhetoric has remained widely underexplored. This essay traces some of the quiet history that energy has played in the rhetorical tradition and charts some points of its ongoing importance.